Diagnosis of Chronic Lymphocytic Leukemia Using iwCLL 2018 Compared with NCI-WG96 Criteria in Cipto Mangunkusumo Hospital: A Practical Consideration in Resource Limited Setting - Lugyanti Sukrisman; Ikhwan Rinaldi (Acta Medica Indonesiana)
Background: The diagnosis of chronic lymphocytic leukemia (CLL) is mainly based on blood count, morphology, and immunophenotyping. In Indonesia, the diagnosis is more challenging as the availability of immunophenotyping tests is limited. The European Society of Medical Oncology (ESMO) stated flowcytometry as a prerequisite to establishing diagnosis of CLL, meanwhile in the original International Workshop on Chronic Lymphocytic Leukemia (iwCLL) 2018 criteria, which has been widely accepted by physicians caring for patients with CLL,  the diagnosis of CLL can be made in patients with cytopenia using bone marrow biopsy where flowcytometry test is not available. The aim of the study was to compare the utility of International Workshop on Chronic Lymphocytic Leukemia 2018 [iwCLL 2018 (2)] compared with National Cancer Institute Working Group 96 (NCI-WG96) criteria in the diagnosis of CLL in Indonesia, especially in limited resource settings. Methods: The data of newly diagnosed CLL patients, including baseline demographic, clinical, and laboratory characteristics was retrieved retrospectively from medical records in Cipto Mangunkusumo General Hospital from 2015 until 2021. Diagnosis of CLL  using iwCLL 2018 diagnostic criteria were then compared with National Cancer Institute Working Group 96 (NCI-WG96) criteria.  Results: Thirty-eight patients were enrolled to this study. The median age was 59.5 years and dominated by males. Most of them were classified in the late-stage disease (63.4% in Binet C and about 70% in Rai III-IV). Four cases were CD5-negative CLL. Based on NCI-WG96 guideline, only 24 patients (63.2%) fulfilled all four criteria for CLL. Similarly, using the iwCLL 2018 flowcytometric criteria without biopsy data, 26 patients (68%) were diagnosed as CLL.   However, if bone marrow biopsy in patient with cytopenia was taken into account, all patients (100%) can be confirmed as CLL. Conclusion: The iwCLL 2018 criteria which included bone marrow biopsy in the presence of cytopenia was more applicable to establish the diagnosis of CLL in Indonesia where flowcytometry is not available.